Latent profile analysis of spinal deep muscle strength and physical fitness in elite Taekwondo athletes - Lee, J.-H.; Kim, T.; Lee, M.; Ha, M.-S. (BMC Sports Science, Medicine and Rehabilitation, 2024)
In Taekwondo, core stability and physical fitness are vital for performance, with spinal deep muscles playing a key role. This study explored the relationship between spinal deep muscle strength and physical fitness in 104 adolescent Taekwondo athletes, using a cross-sectional design in a laboratory setting. Participants were classified into groups based on spinal muscle strength at various angles, measured with a Centaur 3D machine. Outcome measures included body composition (height, weight, BMI) and physical fitness (grip strength, back muscle strength, endurance, flexibility, balance, and leg strength). Latent profile analysis identified five profiles: G2 and G4 showed higher body weight and skeletal muscle mass, with G2 also having the highest grip, back, and leg strength. No significant relationship was found between spinal muscle strength and balance. The findings suggest spinal muscle strength and physical fitness do not always correlate, highlighting the need for further research to optimize training.